Academic Language Mastery - Calderon, Margarita Espino (SAGE Publications, 2016)
By now it's a given: if we're to help our ELLs and SELs access the rigorous demands of today's content standards, we must cultivate the "code" that drives school success: academic language. Look no further for assistance than this much-anticipated series from Ivannia Soto, in which she invites field authorities Jeff Zwiers, David and Yvonne Freeman, Margarita Calderon, and Noma LeMoine to share every teacher's need-to-know strategies on the four essential components of academic language. The subject of this volume is vocabulary. Here, Margarita Calderon reveals how vocabulary is best taught as.